Ultra-minimum contrast percutaneous coronary intervention for a patient with complex coronary artery disease and end-stage diabetic nephropathy. Issue 6 (June 2021) - Shibata, Keita; Wakabayashi, Kohei; Kosaki, Ryota; Sato, Chisato; Nishikura, Tenjin; Shinke, Toshiro; Tanno, Kaoru
Abstract: A pivotal trial indicated that an initial invasive strategy did not improve the clinical outcomes in patients with moderate or severe ischemic heart disease and advanced chronic kidney disease (CKD) as compared with an initial conservative strategy. It is well known that contrast-induced nephropathy (CIN) is associated with worse prognosis after percutaneous coronary intervention (PCI). Minimum contrast PCI may lower the risk of CIN and improve the clinical outcomes of ischemic heart disease and advanced CKD. Here we report a case involving a 46-year-old woman with ischemic cardiomyopathy who was scheduled to start hemodialysis for end-stage diabetic nephropathy but exhibited improved renal function in accordance with the left ventricular function after PCI with an extremely low contrast dose. Accordingly, dialysis was not performed, and the patient did not require it for >2 years after coronary revascularization. The present case supports aggressive examination and revascularization for severe heart failure with an extremely low amount of contrast, even if the patient has complex coronary lesions and end-stage CKD. <Learning objective: It is important to treat with aggressive examination and revascularization for severe heart failure with an extremely low amount of contrast, even if the patient has end-stage chronic kidney disease (CKD). The technique of catheterization with minimum contrast is required for a special patient group. Coronary revascularization with an extremely small amount of contrast medium could improve renal function in patients with end-stage CKD and severely ischemic cardiomyopathy.>